Longitudinal observations of progressive cardiac dysfunction in a cardiomyopathic animal model by self-gated cine imaging based on 11.7-T magnetic resonance imaging - Saito, Shigeyoshi (Sci Rep, 2017)
The purpose of this study was to longitudinally assess left ventricular function and wall thickness in a hamster model of cardiomyopathy using 11.7-T magnetic resonance imaging (MRI). MRI were performed for six cardiomyopathic J2N-k hamsters and six J2N-n hamsters at 5, 10, 15, and 20 weeks of age. Echocardiography was also performed at 20 weeks. The ejection fraction (EF) at 15 and 20 weeks of age in J2N-k hamsters showed a significant decrease compared with those in controls. Conversely, the end-systolic and end-diastolic volumes in cardiomyopathic hamsters showed a significant increase compared with those in controls. Moreover, the heart walls of J2N-k hamsters at 15 and 20 weeks were thicker than those of controls at end-systole; however, there were no significant differences at end-diastole. Optical microscopy with Masson’s trichrome staining depicted no fibrosis in the control myocardium, although it showed interstitial fibrosis in the 20-week-old J2N-k cardiomyopathic myocardium. There were no differences in EF and the wall thickness observed on MRI and those observed on echocardiography. These results indicate the presence of systolic dysfunction in cardiomyopathic hamsters. Self-gated cine imaging based on 11.7-T MRI can be used for serial measurements of cardiac function and wall thickness in a cardiomyopathic model.